Childhood development in the 21st century: The role of tech-nology in health and technology-based education in Nigeria - Arikpo Sampson Venatius (Proceeding International Conference Of Innovation Science, Technology, Education, Children And Health, 2025)
Technology is drastically changing the health sector and education landscape, generating new opportunities, introducing new applications, and rejuvenating or reinventing classical technologies for childhood development. Understanding the role of technology in health and education is crucial to the development of a child. This paper am at examining the perceptions of health workers and teachers on the role of technology in health and education and whether such role (s) can promote childhood development. A total of 22 participants (10 health workers and 12 teachers) were involved in the study and were sampled using propulsive sampling procedure. A survey research design methodology was used with the average reliability coefficients for the two structured questionnaires stood at 0.79 and 0.74. The data were analyzed using descriptive statistics. The result reveals that technology plays a significant role in healthcare and education and promotes childhood development to a very high extent. Specifically, in health, technology improves the dissemination of health information, facilitates public discourse and dialogue around medical health, and enables remote consultation, diagnosis among others. While, in education, technology helps students learn much better, improves communication and collaboration, provides teachers with more resources and allows children to learn at their own pace among others. Despite the positive roles of technology, the study indicates that must health workers and teachers in Nigeria do not frequently utilize technology tools in their healthcare delivery and the classroom for child’s development. This research provides an up-to-date picture of the situation in Nigeria notwithstanding the challenges faced. However, health and education administrators should investigate the non-frequent use of technology by health and teachers to mitigate it negative effect on young children.